2000
DOI: 10.1093/rheumatology/39.10.1095
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term effects of non‐steroidal anti‐inflammatory drugs in osteoarthritis of the knee: a randomized placebo‐controlled trial

Abstract: NSAIDs significantly reduce overall pain over 4 weeks. This short-term responsiveness is retained, and even after several years of therapy with tiaprofenic acid pain scores increased over 2 weeks when it was changed to placebo. Our results do not show long-term benefits from the use of NSAIDs in OA and the majority of patients had persisting pain and disability despite therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 22 publications
3
48
1
2
Order By: Relevance
“…Four trials did not present mean change data but only before and after means and P values 30 32 44 45. Eleven trials presented data on overall pain on 100 mm visual analogue scales or on a categorical five point scale,3032 37 38 41 42 47 5052 while the 12 remaining trials presented either categorical or continuous data from the WOMAC subscale for pain. All 23 trials reported data on pain intensity, and 11 trials reported data on functional disability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four trials did not present mean change data but only before and after means and P values 30 32 44 45. Eleven trials presented data on overall pain on 100 mm visual analogue scales or on a categorical five point scale,3032 37 38 41 42 47 5052 while the 12 remaining trials presented either categorical or continuous data from the WOMAC subscale for pain. All 23 trials reported data on pain intensity, and 11 trials reported data on functional disability.…”
Section: Resultsmentioning
confidence: 99%
“…Only four trials presented outcome data as the mean difference of change with SD between NSAIDs and placebo groups 34 42 46 48. Fourteen trials presented the mean difference of change for each group with P values, SE of mean, or 95% confidence intervals but not mean differences between groups 31 33 35 – 39 41 43 47 49 – 52.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a long-term randomized trial lasting up to 4 years, 61-63% of patients receiving oral NSAIDs and 50% of those receiving placebo reported adverse events [11]. One systematic review evaluated the ability of COXIBs and other gastroprotective strategies with conventional NSAIDs to reduce upper gastrointestinal risks [12].…”
Section: Oral Nsaidsmentioning
confidence: 99%
“…A previous study that examined patients with mild OA showed the greatest efficacy benefits within 1 month (the first time point assessed) with no further improvement in treatment during a period of 12 months. 34 There is evidence that patients with arthritis allow themselves a "trial period" for treatment determined by their beliefs and expectations. 12 Thus, if efficacy does not meet with expectations, adherence to treatment is negatively affected.…”
mentioning
confidence: 99%